PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN SISTEM KOMPUTER DI SMK - Rini Novita; Syaiful Zuhri Harahap (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2020)
The use of computer-based instructional media at Vocational High School (SMKN) 3 Pariaman is still limited to a media presentation using power point. Along with the advancement of information and communication technology (ICT), a lot of software that can be used to create interactive learning media. The results of the preliminary survey of the implementation of learning system computer at SMKN 3 Pariaman shows that there are no teachers who use interactive learning media with Adobe Director software. ICT facilities and infrastructure such as computers, LCD projectors, and internet at SMKN 3 Pariaman existing one, but have not used optimally. Learning media is one important factor in improving student learning outcomes. The selection of learning media in accordance with the needs and characteristics of students can help students understand the subject matter. This research aims to produce an interactive learning media that valid, practical, and effective to help students to master the subject of System Computer.The research method used was R&D (research and development) by using 4D development model (define, design, develop and disseminate). The results showed that interactive learning media is valid based on the assessment of each aspect by the validator. interactive learning media is considered practical based on observation and responses teacher and student. This shows that, Interactive Learning Media otherwise effective use as a medium of learning in improving student learning outcomes.Keywords: Interactive Learning Media, Sistem Komputer, Adobe Director